The pharmacist is in: The availability and distribution of French-speaking pharmacists in Ontario - Timony, Patrick E.; Waite, Nancy; Houle, Sherilyn; Violette, Richard; Gauthier, Alain P. (Linguistic Minorities and Society, 2022)
Francophones are an official language minority in Ontario with limited access to linguistically concordant healthcare services. Although communication is an important skill in the field of pharmacy, little is known about the availability of French-speaking pharmacists. This secondary data analysis of the Ontario College of Pharmacists registry converted weekly hours worked into full-time equivalents (FTEs) and calculated ratios of pharmacist FTEs per 1,000 population. French-speaking pharmacists tended to offer fewer FTEs in communities with a larger concentration of Francophones, particularly in northern and rural areas, a trend that was not observed among English-speaking pharmacists. This maldistribution of French-speaking pharmacists may limit the ability of official language minority patients to receive pharmacy services in their language of choice. Keywords: English, pharmacists, Francophones, linguistic concordance, geographic distribution, French-language health services

Rethinking the way we measure access to language-concordant health services for minority language populations: a secondary analysis of publicly available physician and population data in Ontario, Canada - Timony, Patrick E.; Belanger, Christopher; Bélizaire, Arlynn; Desilets, Antoine; Gauthier, Alain; Karunananthan, Sathya; Muray, Mwali-Nachishali; Peixoto, Cayden; Fitzsimon, Jonathan Peter; Godfrey, Leanda; Bjerre, Lise M. (BMJ Open, 2025)
Abstract Objective Providing care in a patient’s preferred language improves health outcomes and patient satisfaction. In Ontario, access to French-speaking physicians (FSPs) is estimated using FSP-to-Francophone population ratios and compared with total physician-to-total population ratios. This approach fails to consider the fact that FSPs also serve non-Francophone patients and that Francophones must compete with the entire population to access FSPs. As a result, this approach inaccurately suggests that Francophones have better access to language-concordant care than Anglophones/Allophones. We propose a novel approach to address this issue, enabling unbiased comparisons of access to language-concordant care across linguistic groups. Design This secondary analysis of publicly available data containing linguistic variables for the Ontario population (Statistics Canada, 2021 Census) and for family physicians (FPs) (College of Physicians and Surgeons of Ontario, January 2024) calculated competition-adjusted ratios and probabilities of accessing language-concordant care. Setting Ontario, Canada. Participants Census and publicly available data on FPs (ie, those providing comprehensive family medicine care to the community) and the Ontario population were obtained. Results Province-wide, the crude ratio of FSPs per 1000 Francophones was 3.46. After adjusting for competition, the ratio of FSP per 1000 population was 0.12, compared with a general physicians-per-1000 population ratio of 1.05. Anglophones/Allophones attached to a FP have a 100% probability of receiving care in English compared with an 11.4% probability for Francophones to receive care from a FSP. Expressed otherwise, Anglophones/Allophones are 8.8 times more likely to receive language-concordant care (ie, care in English) than Francophones. Conclusions Although crude physician-to-population ratios overestimate Francophones’ access to FSPs, competition-adjusted ratios and probabilities demonstrate that they are much less likely to access language-concordant care than Anglophones/Allophones. This novel approach has equity implications for health human resources planning and can be applied to other linguistic minority groups and healthcare providers.

Linguistic factors and COVID-19 outcomes among long-term care residents in Ontario, Canada - Reaume, Michael; Batista, Ricardo; Imsirovic, Haris; Bjerre, Lise; Kendall, Claire E.; Bouchard, Louise; Gauthier, Alain P.; Landry, Josette-Renée; Chomienne, Marie-Hélène; Muray, Mwali; Hsu, Amy; Prud'homme, Denis; et al. (BMC Geriarics, 2025)
Abstract Background The COVID-19 pandemic disproportionately affected frail individuals, especially those living in long-term care (LTC) homes. This study examined the role of linguistic factors on COVID-19 related outcomes in LTC homes. Methods We performed a population-based, retrospective cohort study of residents living in LTC homes in Ontario, Canada who were diagnosed with COVID-19 between March 31, 2020 and March 31, 2021. Resident language, obtained from LTC assessments, was used to classify residents into one of the three linguistic groups: Anglophone (English), Francophone (French), and allophone (other language). Language of the LTC home was determined using a person-time representation of the languages spoken by residents within each LTC home. We defined LTC facilities as French homes when Francophone residents contributed more than 25% of the person-days, and allophone homes when allophone residents contributed more than 50% of the person-days. Residents whose language corresponded to the language of the LTC home in which they were living were said to have received language-concordant care, while all other residents were said to have received language-discordant care. The outcomes of this study were ED visits, hospitalizations, and mortality within 90 days. Results We included a total of 26,829 LTC residents (20,315 Anglophones, 1,032 Francophones, and 5,482 allophones) living in 572 LTC homes (502 English, 28 French, 42 allophone) who were diagnosed with COVID-19. LTC residents who lived in language-discordant homes were more likely to have ED visits (adjusted HR 1.12, 95% CI 1.01–1.25) and hospitalizations (adjusted HR 1.15, 95% CI 1.02–1.29) when compared to LTC residents who lived in language-concordant homes. Residents-facility language discordance was not associated with overall mortality (adjusted HR 1.00, 95% CI 0.91–1.10) or in hospital mortality (adjusted HR 1.04, 95% CI 0.88–1.23). Conclusion Residents living in language-discordant LTC facilities experienced more ED visits and hospitalizations following diagnosis of COVID-19. The findings of this study highlight the importance of providing frail, vulnerable individuals with linguistically concordant care.

Reporting on knowledge, attitudes, and behaviours of pharmacists regarding the active offer of French language health services in Ontario: A quantitative survey study - Timony, Patrick; Leone, Arielle; Caron, Carolanne; Giguère, Pierre; Thabet, Pierre; Gauthier, Alain; Waite, Nancy M.; Landry, Christine (Canadian Pharmacists Journal / Revue des Pharmaciens du Canada, 2025)
Background: Patient–provider language discordances can negatively affect the availability, accessibility, acceptability, and quality (AAAQ) of pharmacy services as described by the AAAQ framework. With nearly 600,000 residents of Ontario identifying French as their mother tongue, the active offer (AO) of French language pharmacy services should be provided, yet little is known about pharmacists’ familiarity and use of AO. Methods: Ontario pharmacists completed an online survey measuring their knowledge, attitudes, and behaviours (KAB) regarding the AO for French language services (FLS). Demographics, including ability to converse in French, were collected. KAB AO scores were calculated and compared using descriptive and inferential statistics. Results: A total of 360 pharmacists completed the survey. The majority (65.1%) practiced in a primary care setting, 21.1% spoke French, and 71.8% lived in an area where less than 10% of the population were Francophone. Overall, AO scores were highest for attitude (3.8/5) and lowest for behaviours (2/5) and knowledge (1.8/5). Most pharmacists (62.8%) indicated an interest in AO training. Discussion: Gaps in KAB regarding AO for FLS by Ontario pharmacists resemble those observed throughout the health care system. Further training is suggested to address the lack of knowledge regarding AO, particularly its proactive nature, as well as strategies for its implementation. Conclusion: Although most participating pharmacists demonstrated gaps in AO knowledge and behaviour, many had favourable attitudes toward the importance of AO in the pharmacy setting and agreed that further training would be needed to improve their KAB. Further, the AO can address all 4 elements of the AAAQ framework.